(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Proverbs are an essential component of linguistic and cultural identity, reflecting the worldview, traditions, and values of a nation. This article examines the linguocultural characteristics of English and Uzbek proverbs, analyzing their semantic, cognitive, and pragmatic aspects. The paper explores how proverbs encode moral and ethical norms, comparing English and Uzbek expressions of wisdom through linguistic structures and cultural implications.